2018
DOI: 10.1186/s12885-018-4605-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomal irinotecan with fluorouracil for the treatment of advanced pancreatic cancer, a single institution experience

Abstract: BackgroundEffective treatment options for advanced pancreatic cancer are finite. NAPOLI-1, a phase III randomized trial, demonstrated the efficacy of nanoliposomal irinotecan with fluorouracil/leucovorin (nal-IRI + 5-FU/LV) for the treatment of advanced pancreatic cancer following progression on gemcitabine-based chemotherapy. There are limited additional data on the safety and efficacy of nal-IRI + 5-FU/LV following FDA approval in October 2015. We examined the post-approval safety and effectiveness of nal-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
116
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(142 citation statements)
references
References 34 publications
25
116
0
1
Order By: Relevance
“…While combining fluoropyrimidine with conventional irinotecan did not show a clear clinical benefit, nal-IRI plus 5-FU/LV significantly improved survival compared with 5-FU/LV, and this regimen received regulatory approval. Recent real-world data showed consistent clinical outcomes with nal-IRI plus 5-FU/ LV in patients with mPDAC who had previously received gemcitabine-based chemotherapy [18,19]. Because of the heterogeneity of 1L chemotherapy prior to the administration of nal-IRI plus 5-FU/LV and different treatment lines (from 1st-to 5th-line) when it was used in those studies, however, it is difficult to estimate the efficacy of 2L nal-IRI plus 5-FU/ LV after 1L nab-P+GEM.…”
Section: Discussionmentioning
confidence: 90%
“…While combining fluoropyrimidine with conventional irinotecan did not show a clear clinical benefit, nal-IRI plus 5-FU/LV significantly improved survival compared with 5-FU/LV, and this regimen received regulatory approval. Recent real-world data showed consistent clinical outcomes with nal-IRI plus 5-FU/ LV in patients with mPDAC who had previously received gemcitabine-based chemotherapy [18,19]. Because of the heterogeneity of 1L chemotherapy prior to the administration of nal-IRI plus 5-FU/LV and different treatment lines (from 1st-to 5th-line) when it was used in those studies, however, it is difficult to estimate the efficacy of 2L nal-IRI plus 5-FU/ LV after 1L nab-P+GEM.…”
Section: Discussionmentioning
confidence: 90%
“…The pre-emptive dose reductions seen in this study represent real-world oncology practices, and compared to prior data this does not seem to have produced significantly poorer outcomes than those seen in clinical trials. Specifically, Glassman and colleagues noted a median starting dose of 55 mg/m 2 for nal-iri in their real-world data study, which was not associated with significantly inferior outcomes [19]. Other studies have shown a similar maintenance of effectiveness for different regimens used in advanced pancreatic cancer despite reductions in dose intensity.…”
Section: Discussionmentioning
confidence: 97%
“…The phase 3 NAPOLI-1 trial showed PFS for patients treated with nal-iri/5FU to be 3.1 months and OS 6.2 months [18]. More recently, a retrospective real-world experience was published by Glassman and colleagues that reported PFS of 2.9 months [19]. FOLFIRI lacks phase 3 data in this setting, though retrospective and prospective studies can provide estimates of survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these and our findings, also a study by Glassman and colleagues reported promising survival rates for the sequence Gem/NabP followed by FP/Nal-IRI (mOS 23.0 months). They did not find a significant difference to the sequence FOLFIRINOX followed by Gem/NabP and FP/Nal-IRI (mOS 25.5 months) [29]. Furthermore, in the previously mentioned study by Kordes et al patients who received FOLFIRINOX had a shorter median OS (9.9 months, 95% CI; 8.1-11.7) than previously reported [21].…”
Section: Discussionmentioning
confidence: 75%